USING THINK-PAIR-SHARE TECHNIQUE TO IMPROVE STUDENTS’ SPEAKING ABILITY IN DESCRIBING PLACE - Mariam, Siti; Apriliaswati, Rahayu; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe objective of this research was to improve students? speaking ability in describing place using Think-Pair-Share (TPS) technique for the tenth grade students in class IPA 3 of Madrasah Aliyah Negeri (MAN) 1 Pontianak. This research was a classroom action research. The result showed that the use of Think-Pair-Share technique made the students become more active in speaking activity, particularly in describing place by using English and gave positive response or feedback during teaching and learning process. Think it out in Think activity helped students to use and practice their vocabulary in terms of adjectives which relevant with the topic given. Partners? correction in Pair activity in which students were allowed to give correction of their partner?s mistakes in pronouncing English words helped them to practice their pronunciation as well to pronounce the words with better pronunciation. Turn-taking description in Share activity helped students to practice oral description by using better pronunciation, relevant adjectives and simple present tense correctly. These findings were also supported by the result of students? speaking scores in which the mean score improved from 59,1 in Cycle 1 to 72,6 in Cycle 2 then it was 79,6 in Cycle 3. In conclusion, Think-Pair-Share technique improved students? speaking ability in describing place, particularly in the aspects of pronunciation, the use of adjectives, and the use of simple present tense.Keywords: Speaking Ability, Think-Pair-Share technique, Classroom Action Research.